Factors of premarital sexual activities of literate emerging adults in Nigeria - Mulikat Ladi Abdulqadir Mustapha; Rahmat Nurudeen Shuaib (Universitas Ahmad Dahlan, 2021)
The increasing tolerance of antenuptial sexual acts among youth in contemporary society has directed research interest to its consequences on varying health outcomes. Weighing various negative effects of premarital sexual activities, inquiring the factors enhancing emerging adults’ engagement in these activities is needed. This investigation focused on exploring myriad factors (grouped under six categories) of literate emerging adults’ engagement inbantenuptial sexual acts. This study inquired into these factors utilizing a descriptive survey, gathering data through a validated questionnaire possessing a good reliability index; from literate emerging adults in a Nigerian state. Factor analysis and regression were used for data analysis. Results emphasized all factors considered significant with biological, educational, and personal factors been more significant of literate emerging adults’ sexual activities regardless of religion and ethnic background (except for economic factors). The implication of the findings is sex education planning program is needed for counselors in tertiary institutions and the community. Therefore, literate emerging adults will have an avenue to discuss the burning issue of prenuptial sexual acts and the consequences. Moreover, the sex education planning program will help literate emerging adults to understand and clarify personal values, improve their knowledge and make healthy sexual decisions.